Impact of FONCODES on rural enterprises that change lives in Peru - Wong Copaja, Edgard Enrique (2023)
Today, entrepreneurship is considered a means for governments to promote the economic, social, productive and even cultural development of their countries, but despite the benefits of this trend, there are still many important challenges to overcome for the contribution of entrepreneurship is truly sustainable and effective. Jury (2022) It is where the Cooperation Fund for Social Development (FONCODES) identified as a problem to be solved, the limited opportunities in access to local markets for households with subsistence economies that reside in rural population centers in the high Andean and jungle areas. In this way, the limited technological knowledge of rural family production is sought to be solved as its causes; the low capitalization of family assets; the lack of knowledge of markets for the provision of inputs and services, and the destination of their products, through the implementation of rural agrarian and non-agrarian enterprises, whose audience is rural households with subsistence economies in the mountains and jungle of the country, which FONCODES financial resources are organized and accessed through the Executing Nucleus model. From 2012 to August 2023, FONCODES financed 16,261 ventures, with the amount financed being S/ 169,700,250. As main results, 97% of the implemented enterprises were operational and users in the jungle increased their income by 60.95% and those in the mountains by 72.08%, also 45.59% of ERI participate in expanded markets; allowing the generation and/or preservation of 63,273 family self-employments.